2006
DOI: 10.1258/095646206776790240
|View full text |Cite
|
Sign up to set email alerts
|

Sex work practices and condom use in female sex workers in Sydney

Abstract: The aim of this study was to determine sex work practices and predictors of condom use among female sex workers (SWs) in Sydney. SWs from two centres completed a self-administered questionnaire covering demographic and sexual characteristics and sex work practices. One hundred and forty-eight international (born in Asia) and 141 local SWs (born in Australia, New Zealand or the UK) were recruited. Local SWs saw more clients per shift than international SWs (P = 0.002), but international SWs worked more shifts p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…All papers that reported the results of cross-sectional analyses, although three included longitudinal data 25–27. In total, nine studies were conducted in Europe,28–36 two in Australia,23 37 seven in Southeast Asia,38–43 five in sub-Saharan Africa25–27 44 45 and four in Central and South America 24 46–48. Overall, less than half of the studies (11/26) were designed explicitly to explore the effect of migration on the outcome (table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All papers that reported the results of cross-sectional analyses, although three included longitudinal data 25–27. In total, nine studies were conducted in Europe,28–36 two in Australia,23 37 seven in Southeast Asia,38–43 five in sub-Saharan Africa25–27 44 45 and four in Central and South America 24 46–48. Overall, less than half of the studies (11/26) were designed explicitly to explore the effect of migration on the outcome (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, less than half of the studies (11/26) were designed explicitly to explore the effect of migration on the outcome (table 1). 23 24 30 33 35 37 38 42 46–48…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, non-immigrant FSW reported more sexual contacts per week and low rate of condom use with clients, putting them at a high risk for HIV/STI infection. A recent study reported that local FSW had more clients than international (i.e., immigrant) FSW in Sydney, Australia (Fox et al 2006). On the other hand, illegal drug use was higher among immigrant compared to non-immigrant FSW, despite the small number in this group (2.7%, 28 of 1,047).…”
Section: Discussionmentioning
confidence: 99%